Cloning and sequencing of a Bacteroides ruminicola B(1)4 endoglucanase gene. - Matsushita, O (1990)
Bacteroides ruminicola B(1)4, a noncellulolytic rumen bacterium, produces an endoglucanase (carboxymethylcellulase [CMCase]) that is excreted into the culture supernatant. Cultures grown on glucose, fructose, maltose, mannose, and cellobiose had high specific activities of CMCase (greater than 3 mmol of reducing sugar per mg of protein per min), but its synthesis was repressed by sucrose. B. rumincola did not grow on either ball-milled or acid-swollen cellulose even though the CMCase could hydrolyze swollen cellulose. The CMCase gene was cloned into Escherichia coli, and its nucleotide sequence contained a single open reading frame coding for a protein of 40,481 daltons. The enzyme was overproduced in E. coli under the control of the tac promoter and purified to homogeneity. The N-terminal sequence, amino acid composition, and molecular weight of the purified enzyme were similar to the values predicted from the open reading frame of the DNA sequence. However, the CMCase present in B. ruminicola was found to have a monomer molecular weight of 88,000 by Western immunoblotting. This discrepancy appeared to have resulted from our having cloned only part of the CMCase gene into E. coli. The amino acid sequence of the CMCase showed homology to sequences of beta-glucanases from Ruminococcus albus and Clostridium thermocellum.